The Discipline of Imports in the Light of 1992: The Case of Sweden - Pär Hansson (The Research Institute of Industrial Economics (IUI), 1990)
The paper examines the constraint import competition imposes on the price-cost margins in Swedish manufacturing industries. It addresses two questions. Has the free trade agreement between the EC and EFTA reinforced the disciplinary effect of imports? Are there differences between imports of different origins? The results provide some support for intensified competition of the free trade agreement, even though the disciplinary effect of imports originating from the less developed countries is larger than of imports originating from the developed countries.
Keywords: F14; F15; 330; Manufacturing; Trade; Imports